Effectiveness and Safety of High-Intensity Interval Training in Patients With Type 2 Diabetes - Francois, Monique E. (Diabetes Spectr, 2015)
IN BRIEF Recent research has shown that high-intensity interval training (HIIT) can promote improvements in glucose control and cardiovascular health in individuals with type 2 diabetes. This article summarizes the evidence and highlights the ways in which HIIT might be safely implemented as an adjunct to more traditional exercise approaches.